Relationship of testicular growth and size to age, body weight and onset of puberty in Menz ram lambs - Mukasa-Mugerwa, E.; Ezaz, Z. (Elsevier, 1992)
Describes a method for determining the sex and milk protein genotypes (RELPs) of preimplantation stage bovine embryos using multiplex polymerase chain reaction (PCR). Tests a procedure developed for diagnosing multiple characteristics by genotyping K-casein and B-lactoglobulin in addition to identifying the Y chromosome using only 5 to 6 embryo cells and polymerase chain reaction (PCR;10).